1973
DOI: 10.1159/000221268
|View full text |Cite
|
Sign up to set email alerts
|

The <i>in vitro</i> Demonstration of the Efficacy of Trimethoprim as an Antibacterial Agent in a Comparative Bacteriological Study on the Effects of Trimethoprim, Sulfamethoxazole and the Combination Trimethoprim/Sulfamethoxazole

Abstract: The minimal inhibitory concentrations of trimethoprim (TMP), sulfamethoxazole (SMZ) and the combination trimethoprim/sulfamethoxazole (TMP/SMZ) in a ratio of 1:20 have been determined for 97 bacterial strains (66 Escherichia coli, 13 Proteus mirabilis, 22 Enterococcus, 12 Staphylococcus, 4 Klebsiella and Enterobacter and 4 others) using the agar-dilution technique. The same strains and an additional 31 strains were tested for sensitivity to TMP/SMZ and SMZ by the agar-diffusion test. 48 of them were also exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This finding is in contradiction to the former ones. Since we were in agreement with KOchler's and K o ch's [5] point of view about the insufficiency of detailed clinical and experimental trials to eluci date the superiority of the TMP/SMZ combination on the sole use of TMP, the present investigation was carried out. In this study, preventive effects of TMP and sulphamethoxazole (SMZ) alone and combined on the development of experimental hematogenous pyelonephritis in rats were investigated.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…This finding is in contradiction to the former ones. Since we were in agreement with KOchler's and K o ch's [5] point of view about the insufficiency of detailed clinical and experimental trials to eluci date the superiority of the TMP/SMZ combination on the sole use of TMP, the present investigation was carried out. In this study, preventive effects of TMP and sulphamethoxazole (SMZ) alone and combined on the development of experimental hematogenous pyelonephritis in rats were investigated.…”
supporting
confidence: 67%
“…Bacteri cidal action of this combination is due to the blockade of folate synthesis in bacteria concomitantly during two successive phases [1,2]. Although the synergy of the two components is reflected in an often appreciable de crease in the level of minimum inhibitory doses and bactericidal doses in in vivo and in vitro experiments [3,4], K uchler and K och [5] have re cently reported that according to the results of their experiments in vivo the inhibitory effect of trimethoprim (TMP) alone equaled to the effect of the combination. This finding is in contradiction to the former ones.…”
mentioning
confidence: 99%
“…The bacterial count was determined semiquantitatively by spreading 0.01 ml urine evenly on a sheep-blood agar plate and by counting the colonies after 18 h of incubation at 37 °C [28].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper [28] we reported on comparative studies on the antibacterial action of trimethoprim (TMP), sulfamethoxazole (SMZ), and their combination (TMP/SMZ) in vitro. We concluded that TMP alone is often as effective as its combination with SMZ.…”
Section: Introductionmentioning
confidence: 99%